Emergence of multi-drug-resistant Mycobacterium tuberculosis in Niger: A snapshot based on whole-genome sequencing - Zelika Harouna Hamidou; Madjid Morsli; Saidou Mamadou; Michel Drancourt; Jamal Saad (Public Library of Science (PLoS), 2022)
Background Among other West African countries experiencing the high endemicity of deadly tuberculosis, the situation in Niger is poorly evidenced by microbiological investigations. Methodology/Principal findings The study of 42 isolates of Mycobacterium tuberculosis from Niger by whole genome sequencing using Illumina iSeq technology yielded four M. tuberculosis lineages: Indo-Oceanic L1 (n = 1) (2.3%), East-Asian (n = 1) (2.3%), East-African Indian L3 (n = 2) (4.7%) and Euro-American L4 (n = 38) (90.4%). The sub-lineage L4.1.3 comprising 18 isolates (47.3%) was predominant, followed by the L4.6.2.2 sub-lineage (Cameroon genotype, n = 13 isolates) (34.2%). Investigating drug resistance profile for 12 antibiotics found 8/42 (19%) pan-susceptible isolates and 34/42 (81%) resistant isolates; with 40/42 (95.2%) isolates being susceptible to clofazimine-bedaquiline. Conclusions/Significance These unprecedented data from Niger highlight the dynamics of tuberculosis transmission and drug resistance in Niger and may assist tuberculosis control in this country which continues to support a high burden of tuberculosis. Author summary Tuberculosis is a major public health problem in Niger, in West Africa. Niger has an emerging problem with multidrug-resistant tuberculosis (MDR-TB). Whole genome sequencing was used to understand the epidemiology of tuberculosis and genetics of multi-drug resistance among patients from the regions in Niger. In this study, most isolates of M. tuberculosis from this dataset belonged to the L4.6.2.2 sub-lineage and L4.1.3 sub-lineage within the Euro-American lineage. Thirty-four out of 42 (81%) isolates were detected as resistant isolates. Our study highlights the need for epidemiological surveillance and more concerted efforts to ensure that patients are put through treatment.